2017
DOI: 10.21849/cacd.2016.00080
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Characteristics of Fricatives /s/ and /∫/ Produced by Speakers with Parkinson’s Disease

Abstract: PurposeThis study investigated acoustic characteristics of fricatives produced in a repeated syllables task by speakers with Parkinson’s disease (PD), focusing on temporal, intensity, and spectral moment analyses.MethodsTen participants with PD and nine neurologically-healthy participants were asked to repeat the two words, sigh and shy, ten times in a row and at a comfortable rate. Acoustic measurements were made for duration and intensity of each fricative and vowel, plus four coefficients of spectral moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A more recent study on fricatives also focused on sibilants /s, ʃ/ such as Kim (2017) which found that the duration and intensity of fricatives from dysarthric speakers with Parkinson's disease are significantly different than healthy speakers. More varied results were found in spectral moment measurements.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study on fricatives also focused on sibilants /s, ʃ/ such as Kim (2017) which found that the duration and intensity of fricatives from dysarthric speakers with Parkinson's disease are significantly different than healthy speakers. More varied results were found in spectral moment measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Interest has been recently devoted to the articulation approach and the acoustic characterization of different phonemes. In this context, [19] investigated the properties of fricatives produced by PDPs, as these consonants are commonly mispronounced in dysarthric patients [20]. The authors analyzed a corpus including 10 PDPs and 9 HCs repeating two English words (sigh and shy) ten times.…”
Section: Related Workmentioning
confidence: 99%
“…As for the spectral moments, they have been employed in several studies for the characterization of dysarthric speech [19], [20]. We employed four spectral moments: mean spectral peak, which measures whether most energy is concentrated in a small band or dispersed over a wider range; spectral standard deviation, which is a measure of deviation of the spectrum frequencies from the centre of gravity; spectral skewness, which measures the shape of the spectrum below the mean peak compared to the frequencies above it; spectral kurtosis, which describes the weakness of the energy distribution, with positive and negative values suggesting well defined spectral peaks and a flat distribution [20].…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consonants distortion across various diseases have been typically assessed using perceptual evaluation [8,9,10,11,12,13,14]. During the last 2 decades, a considerable effort has been produced to develop objective measures that assess consonant distortions in PD [15,16,17,18,19,20,21,22]. In these studies, voice onset time (VOT) has been the most analyzed feature but with rather contradictory outcomes [23,24,17,20].…”
Section: Introductionmentioning
confidence: 99%